(-2, 4)
Step-by-step explanation:
The given equations:
3x - 2y = - 14 ...(1)
5x + 10y = 30 ...(2)
Using substitution method:
From equation 1:
3x - 2y = -14
3x = 2y - 14
![\begin{gathered} \text{divide both sides by 3:} \\ x=(2y)/(3)-(14)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5yfldv4mospbx3ah5og2gflhf68iu9kpb0.png)
substitute for y in equation 2:
![\begin{gathered} 5((2y)/(3)\text{ - }(14)/(3))\text{ + 10y = 30} \\ (10y)/(3)\text{ - }(70)/(3)\text{ + 10y = 30} \\ \text{Multiply by 3:} \\ 3((10y)/(3))\text{ -3( }(70)/(3)\text{ )+ 3(10y) = 3(30)} \\ 10y\text{ - 70 + 30y = 90} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5f9jirev523nn0omv9s0wouwbj1eykwbsx.png)
![\begin{gathered} \text{collect like terms:} \\ 10y\text{ + 30y - 70 = 90} \\ 40y\text{ - 70 = 90} \\ 40y\text{ = 90 + 70} \\ 40y\text{ = 160} \\ \text{divide both sides by 40:} \\ (40y)/(40)=(160)/(40) \\ y\text{ = 4} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8cfuidgh00zqtmqo1kgrwrvv26b7toc2fn.png)
substitute for y in equation 1:
![\begin{gathered} 3x\text{ - 2(4) = -14} \\ 3x\text{ - 8 = -14} \\ \text{add 8 to both sides:} \\ 3x\text{ = -14 + 8} \\ 3x\text{ = -6} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/sny3lyk4jadwpk2rs10y7tkk76dulk4g6f.png)
![\begin{gathered} \text{divide both sides by 3:} \\ (3x)/(3)\text{ = }(-6)/(3) \\ x\text{ = -2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/m2p5ojn9mo7syzw8g3qwwt55a844kge40z.png)
The solution in ordered pair (x, y) is (-2, 4)